Identifikasi dan Penanganan Sapi yang Terkena Penyakit Mulut dan Kuku (PMK) di Legung Barat Kecamatan Batang-Batang Kabupaten Sumenep - Wahyuni, Nufitri; Ferdiansyah, Akhmad (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2025)
Foot and Mouth Disease (FMD) is an outbreak caused by the Aphtovirus virus and is experienced by ruminant livestock. FMD in the Legung Barat area, Batang-Batang, Sumenep usually occurs during the transitional season or weather. The entry and exit of livestock to the animal market is one of the factors of FMD transmission in livestock. The purpose of this study was to determine the physical condition of cattle and the population of cattle affected by FMD in the Legung Barat area, Sumenep. The study was conducted using a qualitative descriptive method, using case study methods, interviews, direct observation in the field and data collection obtained through field notes. The results of this study showed a cattle population of 200 heads and 60 heads were affected by FMD. Treatment was carried out using traditional and modern methods. FMD can cause economic losses for cattle farmers in the Legung Barat area because the cattle that are raised will be traded. Therefore, farmers must pay more attention to the cleanliness and health of cattle. One way to prevent FMD is to vaccinate before the cattle are infected with the disease and farmers must always ensure that the cattle are in good health.